Contrast-Enhanced Ultrasonography Enables the Detection of a Cold Pressor Test-Induced Increase in Renal Microcirculation in Healthy Participants - Hendriks-Balk, Mariëlle C.; Damianaki, Aikaterini; Polychronopoulou, Erietta; Brito, Wendy; Pruijm, Menno; Wuerzner, Gregoire (Frontiers in Cardiovascular Medicine, 2022)
Background: Renal microcirculation is essential for regulation of the glomerular filtration rate, the reabsorption of salt and water from the interstitium, and hence the blood pressure. Renal ultrasonography coupled to Doppler analysis and contrast-enhanced ultrasound enables the study of renal perfusion. So far, physiologic interventions have rarely been performed to assess the renal perfusion. The objective of our study was to measure the renal perfusion in response to a cold pressor test (CPT). Methods: Healthy adult participants were exposed to a two minutes CPT or a sham exposure (body temperature). Systemic hemodynamics, renal resistive index (RRI) and renal perfusion index (PI) were measured before and during the CPT or the sham exposure. Renal responses were compared using a paired Student’s t-test or Wilcoxon signed rank test. Pearson correlation test was used to test association of variables of interest. Results Forty-one normotensive participants (21 women) were included in the study. Mean blood pressure and heart rate both increased with the CPT. The RRI decreased from 0.62 ± 0.05 arbitrary units (AU) to 0.60± 0.05 AU (p<0.05) and the PI increased from 1930 AU (1310-2830) to 3560 AU (2170-6400) (p<0.05). Compared to the sham exposure, the increase in PI (+79% (42-106) with the CPT was more marked. There was a negative association between the increase in heart rate and mean blood pressure with the RRI (r:-0.550, p=0.002 and r:-0.395, P=0.016), respectively. Conclusion Doppler Ultrasound and CEUS enable the detection of physiological changes within the macro and microvascular renal circulation. The CPT decreases the RRI and increases the PI. Whether these changes are present in pathological state such as diabetes or hypertension will need additional studies.